Implementasi Multikultural Dalam Pembelajaran IPS - Tati, Andi Dewi Riang (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This research aims to understand the reality of multicultural values ​​in today's young generation, analyze the influence of gadgets and the internet in the lives of school-aged children, and identify the need for multicultural education for students. Furthermore, this research uses a qualitative descriptive research method, where the author is required to be able to analyze a phenomenon or social event that is being observed. The research results show that many school children today are exposed to intolerant, discriminatory and even violent behavior. From this social media, various behaviors that deviate from the multicultural values ​​of the Indonesian nation are spread. Ideally, the implementation of multicultural education is expected to be able to act as a shield to prevent conflict due to differences in background. Implementation of multicultural education into social studies (Social Sciences) learning can be done through the following steps: Understanding multicultural concepts, curriculum alignment, use of multicultural-based teaching materials and resources, use of diverse learning approaches, formation of an inclusive learning environment, teacher training, Evaluation and Monitoring, Community Engagement